The Relationship between Self-Esteem and Nomophobia Among Students in Yogyakarta - Oktavian, Bagas; Dewi, Ros Patriani; Aziza, Maghfira Nur; Wedadjati, Ratna Sesotya (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the relationship between self-esteem and nomophobia, an overreliance on smartphones that can impact psychological well-being, among university students in Yogyakarta. With 100 respondents from various universities, the research examines whether higher self-esteem is associated with lower levels of nomophobia. Data were collected through a 34-item self-esteem scale and a 20-item nomophobia scale. Analytical methods included descriptive analysis, classical assumption tests, and hypothesis testing. Results showed a significance value of 0.000 < 0.05 and a correlation of -0.878, indicating a strong negative relationship between self-esteem and nomophobia. Students with higher self-esteem exhibited lower dependency on smartphones, suggesting they are more inclined to engage in face-to-face interactions and are less reliant on digital communication.